Psychosocial factors and excessive gestational weight gain: The effect of parity in an Australian cohort. (January 2016) - Hartley, Eliza; McPhie, Skye; Fuller-Tyszkiewicz, Matthew; Briony Hill,; Helen Skouteris,
Abstract: Objectives: psychosocial variables can be protective or risk factors for excessive gestational weight gain (GWG). Parity has also been associated with GWG; however, its effect on psychosocial risk factors for GWG is yet to be determined. The aim of this study was to investigate if, and how, psychosocial factors vary in their impact on the GWG of primiparous and multiparous women. Design/Participants: pregnant women were recruited in 2011 via study advertisements placed in hospitals, online, in parenting magazines, and at baby and children's markets, resulting in a sample of 256 women (113 primiparous, 143 multiparous). Participants completed questionnaires at 16–18 weeks' gestation and their pregravid BMI was recorded. Final weight before delivery was measured and used to calculate GWG. Findings: the findings revealed that primiparous women had significantly higher feelings of attractiveness (a facet of body attitude; p =0.01) than multiparous women. Hierarchical regressions revealed that in the overall sample, increased GWG was associated significantly with lower pre-pregnancy BMI (standardised coefficient β =−0.39, p <0.001), higher anxiety symptoms ( β =0.25, p= 0.004), and reduced self-efficacy to eat a healthy diet ( β =−0.20, p= 0.02). Although higher GWG was predicted significantly by decreased feelings of strength and fitness for primiparous women ( β =−0.25, p =0.04) and higher anxiety was related significantly to greater GWG for multiparous women ( β =0.43, p <0.001), statistical comparison of the model across the two groups suggested the magnitude of these effects did not differ across groups ( p >0.05). Conclusions/Implications for practice: the findings suggest that psychosocial screening and interventions by healthcare professionals may help to identify women who are at risk of excessive GWG, and there may be specific psychosocial factors that are more relevant for each parity group.